High-resolution carbon isotope changes in the Permian-Triassic boundary interval, Chongqing, South China; implications for control and growth of earliest Triassic microbialites - Mu, X; Kershaw, S; Li, Y; Guo, L; Qi, Y; Reynolds, A (Journal of Asian Earth Sciences, 2009)
High-resolution delta13C_CARB analysis of the Permian-Triassic boundary (PTB) interval at the Laolongdong section, Beibei, near the city of Chongqing, south China, encompasses the latest Permian and earliest Triassic major facies changes in the South China Block (SCB). Microbialites form a distinctive unit in the lowermost 190 cm above the top of the Changhsing Formation (latest Permian) at Laolongdong, comparable to a range of earliest Triassic sites in low latitudes in the Tethyan area. The data show that declining values of delta13C_CARB, well-known globally, began at the base of the microbialite. High positive values (+3-4 ppt) of delta13C_CARB in the Late Permian are interpreted to indicate storage of 12C in the deep waters of a stratified ocean, that was released during ocean overturn in the earliest Triassic, contributing to the distinctive fall in isotope values; this interpretation has been stated by other authors and is followed here. The 13CCARB curve shows fluctuations within the microbialite unit, which are not reflected in the microbialite structure. Comparisons between microbialite branches and adjacent micritic sediment show little difference in delta13C_CARB, demonstrating that the microbialite grew in equilibrium with surrounding seawater. The Early Triassic microbialites are interpreted to be a response to upwelling of bicarbonate-rich poorly-oxygenated water in low latitudes of Tethys ocean, consistent with current ocean models for the PTB interval. However, the decline of delta13C_CARB may be due to a combination of processes, including productivity collapse resulting from mass extinction, return of deep water to ocean surface, oxidation of methane released from methane hydrate destabilisation, and atmospheric deterioration. Nevertheless, build-up of bicarbonate-rich anoxic deep waters may be expected as a result of the partial isolation of Tethys, due to continental geography; release of bicarbonate-rich deep water, by ocean upwelling, in the earliest Triassic may have been an inevitable ...